The Hellenic Marine Observing, Forecasting and Technology System—An Integrated Infrastructure for Marine Research - Evi Bourma; Leonidas Perivoliotis; George Petihakis; Gerasimos Korres; Constantin Frangoulis; Dionysios Ballas; Vassilis Zervakis; Elina Tragou; Petros Katsafados; Christos Spyrou; Manos Dassenakis; Serafim Poulos; et al. (Journal of Marine Science and Engineering, 2022)
Research infrastructures have been established throughout Europe in order to create robust organizations that will facilitate and enhance research and innovation processes and will advance society with innovative products and services. The Hellenic Integrated Marine Observing, Forecasting and Technology System (component of HIMIOFoTS RI) has been implemented in the framework of the National Roadmap for Research Infrastructures to form a large-scale infrastructure for the marine environment in Greece. It links together ocean observing and forecasting systems, coastal zone monitoring and management practices, as well as ocean engineering testing facilities. The overarching framework of the system supports the coordination of five organizations with expertise in the field of marine science and technology, the central management of research activities, and the common development of services and products. It comprises facilities and resources while it provides open access to research communities (academia, industry) to support the scientific advancements and innovation in their fields. The Hellenic Marine Observing, Forecasting and Technology System was further enhanced during its implementation through significant upgrades and developments in order to extend its observing capacity and the forecasting and technological abilities, while advancing the provided services and products.

A High-Resolution Numerical Model of the North Aegean Sea Aimed at Climatological Studies - Ioannis G. Mamoutos; Emmanuel Potiris; Elina Tragou; Vassilis Zervakis; Stamatios Petalas (Journal of Marine Science and Engineering, 2021)
A new, high-resolution model for the northern part of the Aegean Sea, aimed primarily at climatological research (relaxation and data assimilation-free climate simulations), is hereby presented, along with the results of a 28-year-long simulation covering the period from 1986 to 2013. The model applied is the Regional Ocean Modelling System (ROMS). A significant improvement over previous models of the Aegean introduced in this work is the replacement of parameterizations of the Dardanelles exchange by a fully three-dimensional simulation of the flow in the Strait. The incorporation of part of the Marmara Sea in the model domain enables the interaction with other regional climate simulations, thus allowing climatic variability of the exchange of the Mediterranean and Black Seas. An extensive validation is carried out comparing the model output with all the available observations from several different platforms, i.e., satellite sea surface temperature and height, T/S profiles from R/V ships, and HF radar surface currents velocity. We focus on the model’s ability to reproduce, to some extent, the distinct thermohaline features and circulation patterns that characterize this specific area of the Mediterranean Sea. Our findings, after comparing simulation results with all the available observations, revealed the model’s sufficiency to simulate very adequately the complex hydrology of the North Aegean Sea, and the model’s ability to reproduce incidents of deep-water formation that took place in the region in previous decades during the Eastern Mediterranean Transient (EMT).

An integrated open-coastal biogeochemistry, ecosystem and biodiversity observatory of the eastern Mediterranean – the Cretan Sea component of the POSEIDON system - George Petihakis; Leonidas Perivoliotis; Gerasimos Korres; Dionysios Ballas; Constantin Frangoulis; Paris Pagonis; Manolis Ntoumas; Manos Pettas; Antonis Chalkiopoulos; Maria Sotiropoulou; Margarita Bekiari; Alkiviadis Kalampokis; et al. (Ocean Science, 2018)
There is a general scarcity of oceanic observations that concurrently examine air–sea interactions, coastal–open-ocean processes and physical–biogeochemical processes, in appropriate spatiotemporal scales and under continuous, long-term data acquisition schemes. In the Mediterranean Sea, the resulting knowledge gaps and observing challenges increase due to its oligotrophic character, especially in the eastern part of the basin. The oligotrophic open Cretan Sea's biogeochemistry is considered to be representative of a greater Mediterranean area up to 106 km2, and understanding its features may be useful on even larger oceanic scales, since the Mediterranean Sea has been considered a miniature model of the global ocean. The spatiotemporal coverage of biogeochemical (BGC) observations in the Cretan Sea has progressively increased over the last decades, especially since the creation of the POSEIDON observing system, which has adopted a multiplatform, multivariable approach, supporting BGC data acquisition. The current POSEIDON system's status includes open and coastal sea fixed platforms, a Ferrybox (FB) system and Bio-Argo autonomous floats that remotely deliver fluorescence as a proxy of chlorophyll-a (Chl-a), O2, pH and pCO2 data, as well as BGC-related physical variables. Since 2010, the list has been further expanded to other BGC (nutrients, vertical particulate matter fluxes), ecosystem and biodiversity (from viruses up to zooplankton) variables, thanks to the addition of sediment traps, frequent research vessel (R/V) visits for seawater–plankton sampling and an acoustic Doppler current profiler (ADCP) delivering information on macrozooplankton–micronekton vertical migration (in the epipelagic to mesopelagic layer). Gliders and drifters are the new (currently under integration to the existing system) platforms, supporting BGC monitoring. Land-based facilities, such as data centres, technical support infrastructure, calibration laboratory and mesocosms, support and give added value to the observatory. The data gathered from these platforms are used to improve the quality of the BGC-ecosystem model predictions, which have recently incorporated atmospheric nutrient deposition processes and assimilation of satellite Chl-a data. Besides addressing open scientific questions at regional and international levels, examples of which are presented, the observatory provides user-oriented services to marine policy makers and the society, and is a technological test bed for new and/or cost-efficient BGC sensor technology and marine equipment. It is part of European and international observing programs, playing a key role in regional data handling and participating in harmonization and best practices procedures. Future expansion plans consider the evolving scientific and society priorities, balanced with sustainable management.

Acoustic Doppler current profiler observations of migration patternsof zooplankton in the Cretan Sea - Emmanuel Potiris; Constantin Frangoulis; Alkiviadis Kalampokis; Manolis Ntoumas; Manos Pettas; George Petihakis; Vassilis Zervakis (Ocean Science, 2018)
The lack of knowledge of the mesopelagic layer inhabitants, especially those performing strong vertical migration, is an acknowledged challenge. This incomplete representation leads to the exclusion of an active carbon and nutrient pathway from the surface to the deeper layers and vice versa. The vertical migration of mesopelagic inhabitants (macroplanktonic and micronektonic) was observed by acoustical means for almost 2.5 years in the epipelagic and mesopelagic layers of the open oligotrophic Cretan Sea (south Aegean Sea, eastern Mediterranean) at the site of an operational fixed-point observatory located at 1500 m depth. The observed organisms were categorized into four groups according to their migration patterns. The variability of the migration patterns was inspected in relation to the physical and biological environmental conditions of the study area. The stratification of the water column does not act as a barrier for the vertical motion of the strongest migrants that move up to 400 m every day. Instead, changes in light intensity (lunar cycle, daylight duration, cloudiness) and the presence of prey and predators seem to explain the observed daily, monthly and seasonal variability. The continuous presence of these organisms, which are capable of vertical motion despite the profound circulation variability at the site of the observatory, implies their presence in the broader study area. The fundamental implications of the above regarding biogeochemical processing in oligotrophic seas due to the intimate link between the carbon (C) and nutrient cycles, are discussed.